Associated Factors of Treatment Compliance among Hypertensive Patients of Selected Hospital of Rupendehi - Rana, Ikshaya; Shrestha, Pragya; Pokharel, Astha Sharma (Journal of Universal College of Medical Sciences, 2020)
INTRODUCTION: Hypertension is a chronic medical health problem which needs adequate treatment management. It is important to understand the factors affecting compliance in patients to achieve successful treatment compliance. Here study aim to identify the associated factors of medication adherence among hypertensive patients. MATERIAL AND METHODS: We conducted a hospital-based cross-sectional study in UCMS Bhairahawa from April to November 2019. We collected data of 384 hypertensive patients who are in medication of hypertension for at least 6 months. Data was collected by interview method and the medication adherence was measured by eight questions that were developed following the Morisky-Green Test and analyzed by using descriptive and inferential statistics with SPSS software version 22. RESULTS: Good adherence with medication was observed in 58% of the 384 hypertensive patients. Female patients (56.2%) were found to be more likely to adhere to their medication regime, compare to their male patients (43.8%). Multinomial logistic regression indicates that patients who have own house were 6.6 times likely (95% CI: 2.28-19.29 P< 0.00) to adhere; compare to live in rent house. It is also appeared that the patients on medication 6 to 10 years were 0.14 more likely to be compliant compared to the hypertensive patients who were on medication more than 10 years (95% CI: .022-0.94; P<0.043). Availability of the antihypertensive drugs near the house (more than 5 minutes of walking) is important to reduce the poor adherence (OR= 12.2, CI: 1.1-104.1; P<.022). CONCLUSION: Adherence level were higher in female patients who are live in own house having medication for 6 to 10 years. Availability of the hypertensive drugs near to house (more than 5 minutes of walking) is also important to reduce the non-adherence on hypertensive drugs.